Structural, physical and chemical characterization of pineapple harvest fiber (ananas comosus) golden as an alternative to paper processing - Mendoza Cisneros, John Wilder (2020)
The article presents the results obtained in the structural, physical and chemical characterization of the stubble fiber of the pineapple harvest (Ananas Comosus) Golden as an alternative to elaborate paper. The biometric properties of the fibers were determined (length and diameter, wall thickness and lumen diameter), to later obtain the pulp quality indexes for paper, as well as the percentages of cellulose, Holocellulose and lignin, according to the TAPPI Standards for each component and the Jayme-Wise method. This study was made with the purpose of having information for its later use in the pulp and paper industry. Pineapple stubble samples were extracted from the population center of Omaya, Pichari in the Valley of the Apurimac, Ene and Mantaro Rivers (VRAEM) - Peru. The results indicate that they present biometric measurements of: Fiber length: 1105 µm, Wall thickness: 2,75 µm, Fiber width: 20,0625 µm, Lumen diameter: 5,35 µm, that this raw material is suitable to produce regular quality paper presenting a Runkel coefficient of 1,028, a flexibility coefficient of 0,27 and a rigidity coefficient of 0,27; According to its chemical characteristics the fiber of Golden pineapple leaves presents a low content of lignin being 12,335 %, Holocellulose 41,72 % and a high content of cellulose 44,04 % being a potential material in the industry of pulp and paper